Осінній план занять за методом комплексної Арт-терапії «Катарсис» - Бергхауер-Олас Емйовке; Berghauer-Olasz Emőke (Видавництво «Код», 2024)
Резюме. У розумінні арт-терапії процес розвитку або реорганізації особистості можна сформулювати так: взаємодія, кругообіг, направлений зсередини (починаючи з внутрішнього світу) назовні, далі ззовні (від спостереження та інтерналізації явищ і об’єктів зовнішнього світу) всередину.

Abstract. The process of personality development and reorganization in art therapy can be described as a reciprocal interaction, a cycle that moves from the inner world (originating from within) to the outer world, and then from the outer world (observation and incorporation of phenomena and objects from the external world) back to the inner world. In psychological terms, this can be expressed as projection and introjection. This movement, which appears in the creative process, both from the inside out and from the outside in (or vice versa), sets into motion and maintains a kind of psychic metabolism, which is a fundamental condition for recreation and health preservation. This attunement is facilitated by the method of Catharsis Complex Art Therapy, distinguished by its innate harmony with nature, resonating with the rhythm of seasonal changes. Focusing on the alternation of seasons and months sets the psychic dynamics in motion and activates the supposed phase-specific working modes of personality development: splitting (disjunction), differentiation, assimilation, evocation, identification, recognition, projection, introjection, and breakdown, and finally integration and conjunction. Experiencing the subtle changes in the natural environment at an experiential level can give momentum to the circulation of psychic content that encompasses these working modes, which takes place at an increasingly differentiated and higher quality level in the process of personality development, connected to the functioning order of the universe (Antalfai, 2016). The aim of this article is to illustrate the practical application of the Katarzisz Complex Art Therapy method through a workshop plan designed for an autumn month.
Autumn session plan based on the «Katarzisz» Complex Art Therapy
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00014095 Редакційна колегія:https://sites.google.com/uica.education/nayka/%D1%80%D0%B5%D0%B4%D0%B0%D0%BA%D1%86%D1%96%D0%B9%D0%BD%D0%B0-%D0%BA%D0%BE%D0%BB%D0%B5%D0%B3%D1%96%D1%8F?authuser=0 Зміст:https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-8
Keywords: арт-терапія; комплексна арт-терапія «Катарсис»; символи; архетип